Exploring the Associations Between MAP Growth and SBA by Demographics - Durant, January; Wright, Daniel B. (Frontiers in Education, 2022)
MAP Growth (MAP) and Smarter Balanced assessment (SBA) are two of the most common standardized assessments used in Pre-Kindergarten to Grade 12 education in the United States. We show how scores on MAP relate to scores on SBA for third grade students. Previous studies examining the relationship between MAP Growth and SBA have been conducted by the test publisher. The current study expands on this and examines how scores on MAP Growth relate to scores on SBA and examine if these relationships vary by when the MAP Growth assessment is taken or by student demographics (by English language proficiency, gender, and ethnicity). Scores on these assessments are compared for 3rd grade students from Clark County, Nevada, which is the fifth largest school district in the United States. The scale scores were associated and, when using MAP to predict SBA scores, followed a quadratic pattern. While students’ scores on the assessments varied by English language proficiency, gender, and ethnicity (i.e., discrepancies that are often referred to as achievement gaps), the relationships between these assessments showed a similar pattern across these demographics. Growth scores were calculated for three MAP administration time points. As well as showing a slight “rich get richer” effect (i.e., slightly more growth for those scoring high), there were regression towards the mean effects. The MAP growth curves were similar by English language proficiency, gender, and ethnicity.